Bright minds, beautiful ideas : parallel thoughts in different times - Munari, Bruno, 1907-1998; Eames, Charles, 1907-1978; Eames, Ray, 1912-1988 (Amsterdam : Bis, 2003)
The world of design is in confusion. The market suffers from a surplus of products, designers and companies, the majority of which are imitations and epigones that constantly supplant each other. Distinctions between separate disciplines are becoming increasingly blurred, labels merge with one another and design studios go bankrupt. Old and new values clash. The world economy has been plunged into recession while interest for local aspects is on the rise. High time for a rethink on the role of the designer and the meaning of design. What is an actual and true contemporary attitude to design - what is contemporary design? These are questions posed by 'Bright Minds, Beautiful Ideas', an inspiring and brainstorming book that through the imagination and handiwork of four innovative and influential designers, sketches a perspective for today (and possibly the future). Despite differences in background and the date of their oeuvre, Bruno Munari (Italy 1907-1998), Charles and Ray Eames (USA 1907-1978 and 1912-1988), Martí Guixé (Spain 1964) and Jurgen Bey (the Netherlands 1965), share a number of characteristics that are of fundamental importance for design. They question everything and are capable of coupling fantasy, playfulness and investigation with vision. They link culture to economy and science and match curiosity and openness with social commitment and action. Their work and vision are timeless and yet contemporary. 'Bright Minds, Beautiful Ideas' is a vital book that gives a sparkling singular perspective of roles, values and functions of designers and design.
Keywords: Design ; geschiedenis 20ste eeuw